Improving delirium care through early intervention: from bench to bedside to boardroom. Issue 2 (25th January 2013) - O'Hanlon, Shane; O'Regan, Niamh; MacLullich, Alasdair M J; Cullen, Walter; Dunne, Colum; Exton, Chris; Meagher, David
Abstract : Delirium is a complex neuropsychiatric syndrome that impacts adversely upon patient outcomes and healthcare outcomes. Delirium occurs in approximately one in five hospitalised patients and is especially common in the elderly and patients who are highly morbid and/or have pre-existing cognitive impairment. However, efforts to improve management of delirium are hindered by gaps in our knowledge and issues that reflect a disparity between existing knowledge and real-world practice. This review focuses on evidence that can assist in prevention, earlier detection and more timely and effective pharmacological and non-pharmacological management of emergent cases and their aftermath. It points towards a new approach to delirium care, encompassing laboratory and clinical aspects and health services realignment supported by health managers prioritising delirium on the healthcare change agenda. Key areas for future research and service organisation are outlined in a plan for improved delirium care across the range of healthcare settings and patient populations in which it occurs.